Method for preparing copper oxide nanowire material by using dynamic gas phase atmosphere
The preparation of copper oxide nanowires in the field of seawater desalination through dynamic gas phase atmosphere technology solves the problem of difficult to maintain the hydrophilicity and life of the material, achieves higher hydrophilicity and life, expands the application range and improves the photothermal efficiency.
Patent Information
- Application Number
- CN202411307445.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-03
AI Technical Summary
In the field of seawater desalination, the hydrophilicity and life of the materials are difficult to maintain the same consistency. The changes in the proportion of single crystal polycrystalline during the preparation of composite materials lead to a decrease in hydrophilicity, while the structure of electrochemical methods is stable. Insufficient sex and difficult to cope with complex environmental changes.
Using dynamic gas phase atmosphere technology to grow copper hydroxide nanowires on copper nets through chemical deposition, and heat treatment is carried out under oxygen atmosphere to accurately control the oxygen concentration and temperature, regulate the ratio of single crystals and polycrystalline copper oxide, and improve the hydrophilicity of the material. Sex and lifespan.
It realizes precise regulation of copper oxide nanowires, improves the hydrophilicity and life of the material, expands its application range in the field of seawater desalination, and improves the photothermal conversion efficiency and service life.
Smart Images

Figure CN119240777A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of seawater desalination and photothermal materials, and in particular relates to a method for preparing copper oxide nanowire materials by utilizing a dynamic gas phase atmosphere. Background Art
[0002] Solar steam conversion is the use of solar energy to directly evaporate and desalinate water on the surface of a body of water. This new water desalination technology has been widely used. Currently, metal oxide-type photothermal materials have been widely explored and applied in seawater desalination technology. Such materials usually have good thermal localization properties and can effectively increase the evaporation rate of seawater and the photothermal efficiency.
[0003] At present, the preparation technology solutions for metal oxide type photothermal materials include the use of composite materials and the use of electrochemical methods to improve the lifespan. For example, invention patents such as CN118027431A, CN104492490A, and CN118454485A make up for the deficiencies between each material through the compounding of materials, such as combining the high hydrophilicity of metal oxides with other materials with good mechanical stability to obtain photothermal materials with high hydrophilicity and long life. Another type of solution is invention patents such as CN115094497A and CN117947454A, which use electrochemical methods to improve photothermal efficiency and service life by modifying or compounding the surface of the material.
[0004] In the field of seawater desalination, the hydrophilicity of the material interface is one of the key factors that determine its performance. However, the hydrophilicity of metal oxide nanowires produced based on most of the currently disclosed preparation schemes is not consistent in all cases. Its performance is affected by many factors. For example, the multi-step reaction process in the preparation of composite materials will change the single crystal and polycrystalline ratio of metal oxides, resulting in reduced hydrophilicity. Although the electrochemical method for preparing metal oxide photothermal materials can obtain uniform surface morphology and single crystal ratio, its own structure lacks stability and its ability to cope with complex environmental changes is insufficient. Therefore, the development of a simple and convenient method to regulate the hydrophilicity of nanowires and ensure their lifespan, in order to increase their scope of application, enhance photothermal efficiency and lifespan, is a technical problem that needs to be solved urgently. Summary of the invention
[0005] The purpose of the present invention is to propose a method for preparing copper oxide nanowire materials using a dynamic gas phase atmosphere. Through the use of dynamic gas phase atmosphere technology, it is ensured that while improving the hydrophilicity of the material itself, more application scenarios can be achieved in the seawater desalination process and the cost can be reduced. This method improves the hydrophilicity and light absorption performance of the material while simplifying the process flow, providing an innovative material solution suitable for the field of seawater desalination photothermal materials.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing copper oxide nanowire material using a dynamic gas phase atmosphere, comprising the following steps:
[0007] (1) immersing the pretreated copper mesh in a mixed solution of persulfate and hydroxide, and growing copper hydroxide nanowires on the copper mesh by chemical deposition;
[0008] (2) The copper hydroxide nanowires grown on the copper mesh are dried and then heat treated to obtain copper oxide nanowires supported on the copper mesh.
[0009] Furthermore, in step (1), the mesh size of the copper mesh is 100 to 400 meshes.
[0010] Furthermore, in step (1), the pretreatment is to immerse the copper mesh in ethanol and deionized water and ultrasonicate for 10 to 30 minutes, and repeat 1 to 3 times to remove surface impurities.
[0011] Furthermore, in step (1), the mixed solution of persulfate and hydroxide is prepared by mixing a persulfate solution and a hydroxide solution, wherein the volume ratio of the persulfate solution to the hydroxide solution is 1:1; the concentration of the persulfate solution is 0.1 to 0.3 mol / L, and the concentration of the hydroxide solution is 2 to 5 mol / L.
[0012] Furthermore, in step (1), the persulfate is potassium persulfate, sodium persulfate or ammonium persulfate, and the hydroxide is sodium hydroxide, potassium hydroxide, lithium hydroxide or calcium hydroxide.
[0013] Furthermore, step (1) also includes exhausting the mixed solution of persulfate and hydroxide, the gas used is an inert gas, and the exhaust time is 10 to 30 minutes.
[0014] Furthermore, in step (2), the drying temperature is 30°C to 50°C, and the drying time is 20 to 60 minutes.
[0015] Furthermore, in step (2), the heat treatment is to heat treat the copper hydroxide nanowires supported on the copper mesh in a tube furnace under an oxygen atmosphere, and the heat treatment is divided into five stages:
[0016] Stage 1: The temperature was raised from room temperature to 300°C at a rate of 5°C / min, and the oxygen concentration was raised from 1L / min to 3L / min for 60 minutes.
[0017] The second stage: the temperature was increased from 300°C to 400°C at a heating rate of 10°C / min, and the oxygen concentration was increased from 3L / min to 10L / min for 10 minutes;
[0018] The third stage: the temperature is maintained at 400°C, the oxygen concentration is maintained at 10L / min, and the time is 15 minutes;
[0019] The fourth stage: the temperature is naturally cooled from 400°C to 250-300°C, and the oxygen concentration is reduced from 10L / min to 1L / min for 30-60 minutes;
[0020] The fifth stage: The temperature drops from 250-300°C to room temperature by natural cooling, and the oxygen concentration is maintained at 1-3L / min.
[0021] A copper oxide nanowire material prepared by the above method.
[0022] Application of the above copper oxide nanowire material in a seawater desalination device.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The present invention uses dynamic gas phase atmosphere technology to achieve precise control of the ratio of single crystal copper oxide to polycrystalline copper oxide. By finely adjusting the oxygen concentration, the present technology can accurately control the ratio of single crystal to polycrystalline copper oxide nanowires, thereby meeting the needs of application in seawater evaporators.
[0025] (2) The present invention not only optimizes the hydrophilicity of copper oxide nanowires but also enhances the service life of the material by utilizing dynamic gas phase atmosphere technology. The application of this technology enables copper oxide nanowires to have a better long-term life while improving their hydrophilicity.
[0026] (3) The dynamic gas phase atmosphere technology of the present invention significantly expands the application of copper oxide nanowires in fields such as seawater desalination and prolongs their service life. By precisely controlling the oxygen concentration, this technology improves the photothermal conversion efficiency and life of copper oxide nanowires, enabling them to perform well in seawater desalination environments, thereby improving the performance and service life of the overall application. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a SEM microscopic morphology of the copper oxide nanowire material of Example 1;
[0028] Figure 2 This is a flow chart of oxygen flow rate control in Example 1;
[0029] Figure 3 This is a flow chart of temperature control in Example 1;
[0030] Figure 4 This is the optical water drop contact angle measurement result of Example 1. DETAILED DESCRIPTION
[0031] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0032] The present invention discloses a method for preparing copper oxide nanowire materials by using oxygen concentration differentiation technology, which is divided into two steps: preparing copper hydroxide nanowires on a copper mesh by a chemical deposition method and heat treating the copper hydroxide nanowires to obtain copper oxide nanowires. The heat treatment is performed by placing the copper hydroxide nanowires loaded on the copper mesh in a tubular furnace under an oxygen atmosphere. The heat treatment is divided into five stages, as shown in Table 1.
[0033] Generally speaking, higher oxygen concentrations will accelerate the formation of copper oxide nanowires, because higher oxygen concentrations tend to promote the reduction of more copper hydroxide to copper oxide. When the oxygen concentration is high, more defects and grain boundaries will be caused, thereby generating more polycrystalline copper oxide. However, the grain boundaries of the polycrystalline structure may lead to poor material life, and structural degradation is prone to occur at the defects, and the life span is not as good as the single crystal structure during long-term use. Therefore, a lower oxygen concentration should be used for annealing. However, the single crystal copper oxide generated by the lower oxygen concentration has fewer surface active sites than the polycrystalline copper oxide, which affects the hydrophilicity.
[0034] In-depth research has found that the surface of polycrystalline materials has more irregularities and higher chemical activity, which makes it easier for the surface of polycrystalline copper oxide to form hydrogen bonds with water molecules, thereby having higher surface energy and showing good hydrophilicity. In order to ensure hydrophilicity while obtaining a longer material life, it is necessary to accurately control the oxygen atmosphere during the annealing process; mainly to solve the following two problems:
[0035] a. Single crystal copper oxide has good structural life, but poor hydrophilicity:
[0036] Single crystal copper oxide usually shows strong continuity due to the regularity of the surface atomic arrangement, thus achieving a better lifespan. However, compared with polycrystalline copper oxide, it has fewer surface active sites.
[0037] b. Polycrystalline copper oxide has better hydrophilicity, but the structural life is worse:
[0038] Copper oxide with polycrystalline structure grows independently from multiple crystal nuclei during the growth process, thus having more surface active sites and usually showing better hydrophilicity. However, compared with single crystal structure copper oxide, it has more defects and grain boundaries. However, the grain boundaries of polycrystalline structure may lead to poor material life, and structural degradation is prone to occur at defects, so the life is not as good as that of single crystal structure during long-term use.
[0039] Table 1 Changes in time, temperature and oxygen concentration at each stage of heat treatment
[0040]
[0041] The dynamic gas phase atmosphere technology of the present invention achieves fine regulation of the growth process of copper oxide crystals by precisely controlling the oxygen flow rate. This method can solve the problem of the difficulty in precisely controlling the crystal morphology in the prior art, and is particularly good in forming copper oxide nanostructures with specific crystal structures (such as single crystals or polycrystalline).
[0042] Example 1
[0043] The copper oxide nanowire material of this embodiment is prepared by the following steps:
[0044] (1) mixing 100 mL of 0.13 mol / L ammonium persulfate solution and 100 mL of 2 mol / L sodium hydroxide solution to form a uniform mixed solution of ammonium persulfate and sodium hydroxide, immersing the pretreated copper mesh in the mixed solution of persulfate and hydroxide, performing chemical deposition on the copper mesh for 30 minutes by a chemical deposition method to grow copper hydroxide nanowires, and obtaining copper hydroxide nanowires grown on the copper mesh after washing;
[0045] (2) The copper hydroxide nanowires grown on the copper mesh were dried at a temperature of 40° C. for 30 minutes. The dried copper mesh was placed in a tube furnace and heated to 40° C. for 30 minutes. Figure 2 and Figure 3 The annealing process is performed in the steps shown.
[0046] In step (1), the pretreatment is to cut the copper mesh into a size of 50×50 mm and a mesh size of 300, and then immerse the copper mesh in a solution of ethanol and deionized water in a volume ratio of 1:1, ultrasonicate for 15 minutes, and repeat 3 times to remove surface impurities; step (1) also includes exhausting the mixed solution of ammonium persulfate and sodium hydroxide with nitrogen, the gas used is an inert gas, the gas flow rate is 3L / min, and the exhaust time is 30 minutes; the cleaning treatment is to take out the copper hydroxide nanowires grown on the copper mesh and rinse them with deionized water 3 times to remove by-products and impurities on the surface of the copper mesh and the nanowires.
[0047] Example 2
[0048] The same as Example 1, except that the molar concentration of the ammonium persulfate solution is 0.25 mol / L.
[0049] Example 3
[0050] Same as Example 1, except that the molar concentration of the sodium hydroxide solution is 4 mol / L.
[0051] Example 4
[0052] The same as Example 1, except that the sodium hydroxide solution is replaced by a potassium hydroxide solution.
[0053] Example 5
[0054] The same as Example 1, except that the ammonium persulfate solution is replaced by a potassium persulfate solution.
[0055] Comparative Example 1
[0056] The same as Example 1, except that the dynamic gas phase atmosphere method is not used for regulation during the heat treatment process, the heat treatment temperature is 400°C, the heating rate is 5°C / min, and the oxygen flow rate is 2L / min.
[0057] Comparative Examples 2 to 5
[0058] The same as Comparative Example 1, except that the specific information of persulfate and hydroxide is shown in Table 2.
[0059] The copper oxide nanowire material of Example 1 was characterized as follows: Figure 1 The hydrophilicity and seawater desalination performance of the copper oxide nanowire materials of Examples 1 to 5 and Comparative Examples 1 to 5 were tested.
[0060] Table 2 The solutions used in Examples 1 to 5 and the single crystal and polycrystalline ratios and performance results of the copper oxide nanowire materials prepared
[0061]
[0062] Table 3 The solutions used in Comparative Examples 1 to 5 and the single crystal and polycrystalline ratios and performance results of the copper oxide nanowire materials prepared
[0063]
[0064]
[0065] By comparing Table 2 and Table 3, it can be found that the copper oxide nanowire material in the embodiment using the dynamic gas phase atmosphere technology is generally higher in hydrophilicity than the control group. Figure 4As shown, the contact angle of Example 1 is 4.7°, the contact angle range in Table 2 is 4.7-9.22°, and the contact angle of the comparison group in Table 3 is 20.61-34.45°. This shows that the dynamic vapor atmosphere technology effectively increases the proportion of polycrystalline copper oxide in the copper oxide nanowire material, thereby significantly improving the hydrophilicity of the material. At the same time, the dynamic vapor atmosphere technology helps to better regulate the life of the material. The lifespan of the regulated copper oxide nanowires in Table 2 is greatly improved compared to the unregulated copper oxide nanowires in Table 3, indicating that the technology can achieve a better balance between high performance and long life while achieving better hydrophilicity. This means that the dynamic vapor atmosphere technology does not sacrifice the photothermal performance of the copper oxide nanowire material, but better maintains the stability of the copper oxide nanowires through the reasonable combination of single crystal and polycrystalline copper oxide.
[0066] Dynamic gas phase atmosphere technology provides a high degree of process controllability. It can flexibly adjust the temperature and oxygen concentration settings of each stage according to the characteristics of single crystal and polycrystalline copper oxide materials, thereby achieving precise control of the final material properties. This makes the process have a wide range of application potential and can adapt to the complex and changeable preparation needs of seawater desalination materials.
[0067] The testing method involved in the present invention is specifically:
[0068] (1) Hydrophilicity (contact angle) test
[0069] Optical water drop contact angle measurement is an important technology for evaluating the wettability of solid surfaces. Liquid is added to the surface of a solid sample and an optical instrument is used to capture the image of the drop, which is then analyzed using dedicated software to obtain the contact angle. This process requires precise sample preparation, instrument calibration, environmental control, and data analysis to ensure the accuracy and repeatability of the measurement results. This method can be used to qualitatively and quantitatively understand the interaction between liquid and solid surfaces, and then infer the surface energy and potential applications of the material.
[0070] (2) Seawater desalination test
[0071] A seawater evaporator was designed. A polyvinyl alcohol (PVA) sponge with low thermal conductivity was selected as the water-conducting layer to reduce heat diffusion losses. It can absorb seawater by capillary action and transport it to the surface. On top of the water-conducting layer, a hydrophilic copper mesh loaded with copper oxide nanowires was assembled. 2 ) was used to perform a desalination test. The photothermal efficiency was calculated using the evaporation rate of the desalination test automatically collected by an electronic scale.
Claims
1. A method for preparing copper oxide nanowire material using a dynamic gas phase atmosphere, characterized in that: The following steps are involved: (1) immersing the pretreated copper mesh in a mixed solution of persulfate and hydroxide, and growing copper hydroxide nanowires on the copper mesh by chemical deposition; (2) The copper hydroxide nanowires grown on the copper mesh are dried and then heat treated to obtain copper oxide nanowires supported on the copper mesh.
2. The method according to claim 1, characterized in that In step (1), the mesh size of the copper mesh is 100 to 400 meshes.
3. The method according to claim 1, characterized in that In step (1), the pretreatment is to immerse the copper mesh in ethanol and deionized water and ultrasonicate for 10 to 30 minutes, and repeat 1 to 3 times to remove surface impurities.
4. The method according to claim 1, characterized in that: In step (1), the mixed solution of persulfate and hydroxide is prepared by mixing a persulfate solution and a hydroxide solution, wherein the volume ratio of the persulfate solution to the hydroxide solution is 1:1; the concentration of the persulfate solution is 0.1 to 0.3 mol / L, and the concentration of the hydroxide solution is 2 to 5 mol / L.
5. The method according to claim 1, characterized in that In step (1), the persulfate is potassium persulfate, sodium persulfate or ammonium persulfate, and the hydroxide is sodium hydroxide, potassium hydroxide, lithium hydroxide or calcium hydroxide.
6. The method according to claim 1, characterized in that Step (1) also includes exhausting the mixed solution of persulfate and hydroxide, the gas used is an inert gas, and the exhaust time is 10 to 30 minutes.
7. The method according to claim 1, characterized in that In step (2), the drying temperature is 30°C to 50°C and the drying time is 20 to 60 minutes.
8. The method according to claim 1, characterized in that In step (2), the heat treatment is to heat treat the copper hydroxide nanowires supported on the copper mesh in a tube furnace under an oxygen atmosphere. The heat treatment is divided into five stages: Stage 1: The temperature was raised from room temperature to 300°C at a rate of 5°C / min, and the oxygen concentration was raised from 1L / min to 3L / min for 60 minutes. The second stage: the temperature was increased from 300°C to 400°C at a heating rate of 10°C / min, and the oxygen concentration was increased from 3L / min to 10L / min for 10 minutes; The third stage: the temperature is maintained at 400°C, the oxygen concentration is maintained at 10L / min, and the time is 15 minutes; The fourth stage: the temperature is naturally cooled from 400°C to 250-300°C, and the oxygen concentration is reduced from 10L / min to 1-3L / min, for 30-60 minutes; The fifth stage: The temperature drops from 250-300°C to room temperature by natural cooling, and the oxygen concentration is maintained at 1-3L / min.
9. A copper oxide nanowire material prepared by the method according to claims 1 to 8.
10. Use of the copper oxide nanowire material according to claim 9 in a seawater desalination device.
Citation Information
Patent Citations
Zinc oxide-polyaniline composite photocatalytic material with efficient photocatalytic activity and preparation method of zinc oxide-polyaniline composite photocatalyst material
CN104492490A
Metal-based photo-thermal component and preparation method thereof
CN115094497A
Electrocatalytic material with hierarchical structure as well as preparation method and application of electrocatalytic material
CN117947454A
Photo-thermal material based on MOF (Metal Organic Framework), preparation method of photo-thermal material and solar two-stage interface evaporator
CN118027431A
Composite photo-thermal hollow fiber membrane loaded with titanium dioxide and silver as well as preparation method and application of composite photo-thermal hollow fiber membrane
CN118454485A
Cited By
Intelligent production process of magnesium deposition hydrogen storage material
CN120308912A
